Brief Communication: Rapid Assessment of landslide events based on UAV photogrametry: The 9 January 2021 Cimanggung Landslide, Sumedang, Indonesia - Abdurrahman, Ali; Budipraja, Muhammad Ariq; Khoirullah, Nur; Helmi, Faisal; Sophian, Raden Irvan (Journal of Geological Sciences and Applied Geology, 2021)
The landslide incident in Cisarua Village, Cimanggung District on January 9, 2021, is one of the natural disasters which is quite concerning to see the victims. This short mapping is focused on seeing changes in the shape of the affected area and slope faces before the landslide and after the incident. The brief mapping uses the DJI Mavic Pro model UAV that flies at an altitude of 50 meters and 150 meters above the ground with an overlap of 80% and covers an area of 3 ha. Aerial photo processing will produce output in the form of orthophoto images and digital elevation models (DEM) of landslide affected areas. The result of geometric observation showed that the land surface was covered with an area of 3,789 m2. The measured flat length ranges from 120 meters and 32 meters wide. There is also a slope angle after and before the landslide of 2.8 degrees. Analysis of the causes of landslides in terms of geomorphological aspects shows the landslide affected areas that are right in the hilly valleys coupled with buildings that cover the surface water flow from high rainfall. In addition, the analysis of the causes of technical geological analysis shows that landslides can occur due to differences in soil types with different physical properties so that the two soils are not bound by cohesion forces between soils.